A preparação para performance musical de quarteto de violões - Salgado, Rafael Pedrosa [UNESP] (2015)
This work discusses strategies for the preparation of chamber music performance for guitar quartet. The main objective is determine how professionals Brazilian guitar quartets plan and conduct their trials. The methodology consisted of four main steps: 1) a review of the literature on preparation for musical performance in Portuguese and English, where was reviewed on individual performance as the chamber music performance; 2) developing and implementing a questionnaire to guitarists who work or have worked in professionals Brazilian guitar quartets; 3) a survey of the recorded repertoire audio and video by Brazilian quartet, illustrating the practice of transcription and arrangement for this formation and 4) suggestions of rehearsals procedures for guitar quartet, as learning facilitators and the rapport between the musicians in this chamber formation. The main conclusion determines the strategies used by Brazilian guitar quartets in preparing their musical performances and suggests strategies targeted to the specific characteristics of training as means of optimization of that preparation